European student-athletes` perceptions on dual career outcomes and services: Insights from the "Facilitating Higher Education for Athletes - WINNER Education Model" LLP project - Fuchs, P. X.; Wagner, H.; Hannola, H.; Niemisalo, N.; Pehme, A.; Puhke, R.; Marinsek, M.; Strmecki, A.; Svetec, D.; Brown, A.; Capranica, L.; Guidotti, F. (EAS Conference, 2015)
Introduction: The EU guidelines on dual careers (i.e., sport and education) encourage Member States to implement appropriate dual career services for elite student-athletes. In this context, the European "WINNER Education Model" LLP project aims to develop an effective education model for student-athletes. Thus, the purpose of this study was to investigate: i) student-athletes` perceptions regarding their sport and academic career paths; and ii) existing and possible implementations of dual career services. Methods: A 25-item semi-structured questionnaire was undertaken with 221 European elite student-athletes involved in individual and team sports at national and international levels. Results: Differences (p=0.05) for nationality, gender, type of sport, and competition level emerged. Female athletes tended to place higher efforts in their academic career with respect to their male counterpart. Athletes involved in individual sports perceived a low support (<3 pt) from academic staff. Furthermore, international level athletes perceived a higher impact (3 pt) of sport commitment on their academic career with respect to their national counterparts (2.5 pt). Low perceptions (<3 pt) emerged for academic consideration of dual career at academic (2.4-2.7 pt) and sport (2.1-2.9 pt) environments, support of faculty staff (2.2-2.9 pt), and time schedule adaptation at academic (1.6-2.7 pt) and sport (2.4-2.8 pt) levels. The highest positive perceptions emerged for family/friends/peers support (4.0-4.7 pt). In general, student-athletes demanded implementations at academic level (i.e., flexibility, on-line education) and sport support. Discussion: National academic and sports systems have a relevant effect on the student-athletes` perception of their dual career, especially at highest sport level. In particular, student-athletes request academic institutions to provide flexibility and long-distance learning and sport bodies to assist them with tutoring support. Conclusions: The present findings represent valuable insights for facilitating an effective higher education path for student-athletes and other atypical students to be tested within the "WINNER Education Model" project